2018
DOI: 10.1371/journal.pone.0200546
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus DNA modulates regulatory T-cell programming in addition to enhancing interleukin-17A production via Toll-like receptor 9

Abstract: Infection with the Epstein-Barr virus (EBV) has been associated with several autoimmune diseases including rheumatoid arthritis (RA). We have previously reported that DNA from this virus enhances production of the pro-autoimmune interleukin 17A (IL-17A) in mice. In this study we assessed the effect of EBV DNA on regulatory T cell programming and examined whether it mediated its effects via Toll-like receptor 9 (TLR9) in mice; moreover, we evaluated whether EBV DNA in humans had similar effects to those seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…EBV is thought to be involved in several autoimmune diseases since it appears to modulate human immune responses (33). We previously reported that EBV DNA was capable of enhancing the production of the proinflammatory cytokine IL-17A when injected into mice (25); moreover, we observed a linear correlation between EBV DNA and serum IL-17A levels in RA patients (6). Since IL-17A plays a critical role in the pathogenesis of a variety of inflammatory autoimmune diseases, EBV DNA may thus contribute to autoimmune disease development or exacerbation.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…EBV is thought to be involved in several autoimmune diseases since it appears to modulate human immune responses (33). We previously reported that EBV DNA was capable of enhancing the production of the proinflammatory cytokine IL-17A when injected into mice (25); moreover, we observed a linear correlation between EBV DNA and serum IL-17A levels in RA patients (6). Since IL-17A plays a critical role in the pathogenesis of a variety of inflammatory autoimmune diseases, EBV DNA may thus contribute to autoimmune disease development or exacerbation.…”
Section: Discussionmentioning
confidence: 59%
“…In another study, we found that the average serum IL-17A levels were higher in RA patients than in non-RA subjects. In addition, we detected a linear correlation between EBV DNA levels and serum IL-17A levels in RA patients but not in controls (6).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, increased levels of IL-17A and IL-8 were observed in the gastric mucosa of gastric ulcer and non-ulcer H. pylori-infected patients compared to uninfected non-ulcer patients, and both IL-17A and IL-8 are strongly correlated with an increase in neutrophil infiltration in infected patients. Interestingly, serum levels of IL-17 directly correlate with the EBV DNA load in individuals with rheumatoid arthritis, which was not observed in controls, and this IL-17 enhancement, in the course of EBV infection, is mediated by toll-like receptor 9 (TLR9) [34].…”
Section: Biology and Disease Associations Of H Pylori And Ebvmentioning
confidence: 99%
“…The reduction in plasma IL-17A and CCL28 levels after INMEST and the restored MAIT/Regulatory T-cell relationship indicate a modulation of this axis by INMEST treatment and mitigation of an inflammatory state originating at the immune microbe interface in the intestine. Also, the common Epstein-Barr virus, EBV, often associated with ME have been reported to induce IL-17 and reactivation of this virus is another possible chronic immune stimulation in ME-patients (36).…”
Section: Cell-cell Relationships Are Perturbed In Mementioning
confidence: 99%